Guidelines for wetlands ecosystems valuation in the Nile basin - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2016)
Economic valuation of wetland ecosystem services enhances informed public decision making concerning sustainable utilization of the ecosystem. The valuation is particularly crucial where the economic values of wetlands need to be compared directly against the monetary value of alternative public investments. Burullus lake is one of the most vulnerable areas along the delta’s, it is the second largest of the Egyptian northern lakes along the Mediterranean coast declared by Prime ministerial decree 1444 in the year 1998, a protected area. In 1998 Burullus Lake was approved as a RAMSAR site in Egypt, this report aim to clarify the main terms and methodology used by several guidelines to valuate use and non use ecosystem services, two questionnaires were prepared to conduct a new field work for further information about local communities satisfaction toward the fish capture as a market price method and bird watching as a travel cost method. In Mara wetland, Tanzania, economic valuation of ES derived from the wetland remains limited despite the fact that the wetland has been expanding landward over the last five decades. This study reviewed different economic valuation tools used in estimating economic values of wetlands, their limitations and selected the appropriate methods applicable in the case of the Mara wetland. In this case, market price-based methods were used to estimate their values. Other provisioning ES such as water and pasture for livestock however, are not for sale. The monetary values of water and livestock’s pasture were estimated by group valuation method through an FGD consisting of 23 people utilizing the services. Water purification ES of the wetland though assessed in this study was not valued directly to avoid double counting of the service. The willingness to pay for the water provision captures both water quality and quantity. The current (2015/2016) annual total economic value of Mara wetland in terms of provisioning and water purification ES is TZS 39,877,804.22 (USD18, 453.40) of which crop production contributes the highest (47%) value of the TEV while thatching grass contributes the lowest (0.1%). The dinder park of Sudan was declared a National Park at 1935, as Biosphere reserve at 1979 and was designated as Wetland of International Importance (Ramsar site) in 2005. The economic evaluation methods are mainly by direct use and market prices. The Total Economic Value (TEV) produced as result is (92944.22 USD) The economic importance of the wetlands is definite and this TEV is still limited if compared to the real benefits from the different Dinder wetland' ecosystems. In Nakivubo wetland, Uganda the direct use value of the main provisioning services of the Nakivubo wetland Local Communities (one household per hectare per year) is worth about 8,951,809.11Uganda Shillings ($14,833.88).